Decoding hypertensive disorders in pregnancy: a tertiary center experience of risk, delivery, and outcome - Singh, Garima; Patil, Prachi; Shetty, Chiranjeev; Mainani, Aishwarya; Gopal, Sriram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Hypertensive disorders are a major cause of maternal and perinatal morbidity and mortality worldwide. This study aimed to investigate the prevalence, risk factors, clinical manifestations, and maternal and fetal outcomes associated with hypertension in pregnancy. Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynaecology at a tertiary care teaching hospital in Navi Mumbai over a defined study period. Pregnant women diagnosed with hypertensive disorders of pregnancy were included. Clinical and obstetric data were collected, including demographic characteristics, gestational age, parity, mode of delivery, and neonatal outcomes. Data were analyzed using descriptive statistics and appropriate inferential tests, with a p value of <0.05 considered statistically significant. Results: The mean age of participants was 31.04±4.8 years. Most women were multigravida or grand multipara (61.2%). Caesarean section was the predominant mode of delivery (82.7%). The most common neonatal birth weight was between 2 and 2.5 kg (23.5%). No statistically significant association was observed between demographic or obstetric factors and mode of delivery, although obesity showed a trend toward significance (p=0.07). Conclusions: Hypertensive disorders during pregnancy are prevalent and associated with adverse maternal and fetal outcomes. Early identification of risk factors and close monitoring of high-risk pregnancies are crucial for improving outcomes.